Cardiogenic Shock and Guillain–Barré Syndrome as the First Manifestations of Pheochromocytoma - Maryam Heidarpour; Nafiseh Sereshti; Davood Shafie; Bijan Iraj; Hassan Rezvanian (Case Reports in Endocrinology)
Febrile congestive heart failure is a rare first manifestation of pheochromocytoma. Herein, the case of a 31-year-old female with febrile congestive heart failure and subsequent cardiogenic shock is presented. After intensive care unit (ICU) admission and further evaluating the right adrenal mass observed in abdominal ultrasonography, the diagnosis of pheochromocytoma was confirmed. Then, she was scheduled for the right adrenalectomy. Before surgery, she complained of acute-onset progressive muscle weakness in the lower limbs, followed by the upper limbs. After further investigation, she was diagnosed with Guillain–Barré syndrome and treated with intravenous immunoglobulin (IVIG). She recovered well after the right adrenalectomy, and during the subsequent 18 months, the follow-up did not reveal any complications, and left ventricular function recovered to normal.